How Organizational Culture Affects Information System Success: The Case of an Indonesia IT-Based Company - Siti Mardiana; Jann H Tjakraatmadja; Atik Aprianingsih (Universitas Airlangga, 2018)
This research aims at exploring the effect of organizational culture, especially clan culture, toward the success of information system implementation. A conceptual model of information system success had been developed by integrating DeLone-McLean model, technology acceptance model (TAM), unified theory of acceptance and use of technology (UTAUT). Competing values model (CVM) is being used for organizational model, as such the assessment for organizational culture is using organizational culture assessment instrument (OCAI). To test the proposed conceptual model, empirical study was conducted at a IT-based company using questionnaire and gave the total of 319 usable data samples. The data analysis is using SmartPLS3 due to the abnormality of data distribution. The OCAI assessment shows that the company has a tendency toward clan culture which is quite unexpected for an IT-based company. However, further analysis shows that the company has successfully mixed clan culture with the less-dominant types of culture to create a conducive culture for the success of information system implementation. This study sheds light on IT implementation for business organizations especially the ones which have clan culture as a dominant culture embedded in their organizations.